The Development Strategy of the Dragon Fruit Farming Business in Sei Sijenggi Village Reviewed from The Side of Maslahah - Laiyinna Misqha Efendi; Muhammad Arif; Aqwa Naser Daulay (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to identify strategies for developing the dragon fruit farming business in Sei Sijenggi Village using SWOT analysis based on the mashlahah (Welfare) theory. This research was conducted qualitatively and data was collected through observation and interviews. SWOT analysis is used to analyze the collected data. The research found that internal factors consist of four strength factors and four weakness factors, while external factors consist of four opportunity factors and four threat factors. In the SWOT diagram, the combination of the IFAS value of 2.94 and the EFAS value of 2.86 shows that the strategy for developing the dragon fruit farming business in Sei Sijenggi Village is in quadrant 1 from the mashlahah side. This condition shows that it is still in a strategic position to continue to be developed because the strength score is more dominant than the weakness score (easy cultivation and low risk in accordance with the mashlahah principle) and the opportunity score is more dominant than the threat score (potential supporting natural resources). The S-O (Strength-Opportunity) strategy is the main strategy that can be used in this research. However, aggressive strategies were used to support this research.